Hilary Mantel’s Eight Months on Ghazzah Street: The Displacement of British Expatriates in Saudi Arabia - García Hernández, Silvia (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2015)
This article explores how Hilary Mantel portrays the lives of a British expatriate couple, the Shores, who are seen as “others” when they move to a different country, Saudi Arabia, where the socio-political scheme is totally different from those they have previously known. The protagonists’ experience in Saudi Arabia will result in feelings of displacement and marginalisation, and the conditions under which they live make them lose their own identities, to the point of not knowing who they really are. The situation is compounded for the woman protagonist, who also suffers from the consequences of racism and Islamic fundamentalism. Furthermore, the novel also depicts how the Shores are doubly displaced, these feelings also appearing when they are with other British expatriates in Saudi Arabia as well as when they go back to their homeland, England, since they are not considered to belong there anymore. Keywords: displacement; expatriates; belonging; Islamic religion; Saudi Arabia; Hilary Mantel